Executive Committee Minutes 2022-02-10 - Academic Senate:::::::::
Approval of Agenda - Items added: Faculty Eligible for Emeritus status and request for Distinguished Chair Emeritus Status for Greg Sarris. Business Faculty visit postponed. Approved. Minutes of 1/27/22 - Approved. Chair Report. President Report. Provost Report. Statewide Senator Report. Vice Chair Report. Vice President of Student Affairs Report. Student Representative Report. Proposal for the Senate meeting to remain virtual indefinitely - amended and approved for the Senate agenda. Potential Letter regarding support for flexibility for staff - deferred. Continued discussion - Staff and ERFSA members on Ex Com. Senate agenda approved.